If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4x + k = 0 Reorder the terms: k + 4x + 4x = 0 Combine like terms: 4x + 4x = 8x k + 8x = 0 Solving k + 8x = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8x' to each side of the equation. k + 8x + -8x = 0 + -8x Combine like terms: 8x + -8x = 0 k + 0 = 0 + -8x k = 0 + -8x Remove the zero: k = -8x Simplifying k = -8x
| 2-8n=-8(n-2)+2n | | 2m+3=4m+13 | | 2x+9=-47-6x | | b-13=4 | | 20-6x=12-7x | | 2m+4=m+7 | | 6x-1+6x-6+82=180 | | 6x^2=34x-40 | | 20x^2-16x=4x | | 4w/7=56 | | -39=-22+d | | 4a^2+b^2+12a-4b+13=0 | | 6x^2-23=-21 | | 4+7x=-32+x | | 35=7/3w | | -36+8b=4(3+4b) | | a+23=25 | | (5x)+7=-2x | | 2c-10+6= | | -58x-2+6=8x-230.6 | | 262.818/28.26 | | x(2x-2)+x(2x-4)=(4x+7)(x-3) | | (2x^4+7x^3-8)-(7x^2-5x+4)= | | -2-5x=-2(1+4x) | | 1/2*b*19.8 | | 7g+8=22 | | 0.2x=-0.7 | | R=1-2n+5 | | 4x+4x+3=0 | | 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 |